Evidence-Based Instruction in Reading: A Professional Development Guide to Culturally Responsive Instruction - Smith , Jayme (Journal of Interdisciplinary Studies in Education, 2014)
Evidence-Based Instruction in Reading A Professional Development Guide to Culturally Responsive Instruction, written by Robin Wisniewski, Gay Fawcett, Nancy Padak, and Timothy Rasinki, provides teachers information on culturally responsive instruction. This book is one of a five books in a series. Each book in the series lends to one major component of literacy instruction